The Role of Inhouse Travel Arrangers on Purchase of Star Hotel Rooms: A Study with Reference to Kochi,the Commercial Capital of Kerala - Thomas, Ajith K (Journal of Contemporary Research in Management (JCRM), 2016)
Corporate sector is thought to be a source for business to star hotels, especially those hotels locate in commercial cities. The business from this segment comprises of transient visit of executives, organization of conferences, training programmes, long stays related to projects and banquet functions including product launches and incentive programmes. For many major business houses these activities are centralized under one department like Administration, Human Resources (HR), Public Relations (PR), Procurements and Facilities. The persons who handle these travel arrangements from these departments are not buying the hotel services, for their own personal use. Instead, these professionals can influence the hotel room purchases of a boss or by guests, for whom the rooms are being booked. These are most often the secretaries and administration staff members. Many of them handle such activities as an additional responsibility to their existing core task like administration, Human resources, Public relations, and Procurement. They are not intermediaries like travel agents, but do all functions similar to the functions of a travel agent. They negotiate for special rates with hotels, according to the entitlements or eligibilities of each traveling executive from their organization; they prepare the empanelled list of hotels in different cities to accommodate their executives and guests; and further more handle the reservations on behalf of the organization. These corporate travel arrangers also go on to the extent of processing the bills, in case if, the company enjoys credit facility with the hotels. Â  The role of these people, the researcher would like to name, â€˜Informal In house Travel Arrangersâ€™ (IHTAs) in the light of their purchase decision, is not studied yet. There have also been no attempts to develop a scale to find the reasons why these IHTAs choose a particular hotel. Consumer decision making models have been explained by many researchers for the last several years now. The discussions in the literature has been primarily on the perspectives of consumer decision making like the â€˜value perspectiveâ€™, the â€˜information processing perspectiveâ€™, the â€˜emotional perspectiveâ€™, and â€˜cue utilization theoryâ€™. There have also been several attempts in the literature to combine various perspectives together. Most of the attempts were revolving around a single perspective, with an emphasis on the chosen perspective discussing other perspectives in its light. Many researchers have done studies on different perspectives and have concluded that no one perspective, explain, fully the decision making process and they commended that; consumer decision making can only be explained based on several perspectives. Almost all the valuable studies in the field suggested that it is a challenge among marketers to have an understanding of human choice, in the current age (where everyone relies on computers), to arrive at decisions based on information supplied. While looking at the literature on decision makers, it has been observed that, they use multiple criteria like reasons, cost benefit calculations and affect, to arrive at their decisions (Weber 1998). Â  Based on these understandings, some researchers suggest that there should be a framework which integrates various perspectives, to explain decision making (e.g. Hansen 2005). He integrated the different perspectives and called it a â€˜hybrid modelâ€™ and suggested that decision making can be partly explained with the help of this framework. Thus, only very few attempts were made to model and incorporate different perspectives to explain decision making (Weber et al. 1998). The best attempt can be seen in the argument of Hansen (2005), where he combines the several perspectives and proposes a framework. The combined hybrid model is tested using two experimental designs and he proposes a model. In this model, he combines the several perspectives and argues that each one of the value perspective, the information perspective, the cue utilization theory and the emotional perspective, combines in varied degrees and leads to the buying decision. Â  These combinations in varied proportions lead to the purchase decision. He did not claim that this is a comprehensive model and calls further researches in the area to identify or propose extension models. He specifically calls for researchers to examine the other perspectives, which may have been elusive in his study. This is where the researcher has embarked upon to find the elusive â€œsurrogate factorâ€ for hotel room bookings for guests in luxury hotels. The researcher proposes a new model, which is a hybrid model with a slight extension of Hansenâ€™s model and calls it â€œSurrogate modelâ€. This model is a simpler model and it also captures the factors of â€˜surrogateâ€™ buying behavior in the purchase decision. The researcher did not stop with this new theory development by introducing the â€œSurrogate factorâ€, but also created a scale which can measure the three factors namely, Personal, Cue utilization factor and the Surrogate factor. He also tested the model using exploratory and confirmatory tests. Â  The researcher conceptualized, purchase decision as a second order one-dimensional construct comprising of three important reflective components: Personal, Cue utilization and Surrogate factors. Other hypotheses when tested yielded results that there is no relation between Intention to purchase hotel rooms by IHTA and gender, type of industry represented by the IHTA, the age group they belong, their booking experience, the occurrence of booking activity and the productivity of the company in terms of room bookings for the year. The methodology followed is a 7 step process for developing the IPHRI scale. It sub assumes testing of the proposed model. The steps followed are Step 1 - Construct definition and content domain, Step 2- Item Generation, Step 3-Editing the scale items, Step 4-Pilot study 1, Step 5- Exploratory survey and EFA, Step 6- Pilot study 2 and Step 7-the Confirmatory survey and CFA. Â  The researcher has identified the 3 factors in the EFA as Personal factor, Cue Utilization factor and Surrogate factor. The hypothesis tests proved that the Intention to Purchase Hotel Rooms by In-house Travel Arrangers (IPHRI) scale was a second order construct. It was confirmed that the 3 factors is a linear combination as Factor 1: Personal factor, Factor 2: Cue utilization factor and Factor 3: Surrogate factor. In Confirmatory Factor Analysis, the pattern of loadings of the measurement items on the latent constructs is explicitly specified in the model. The fit of this pre-specified model is examined to determine its convergent and discriminant validities. This factorial validity deals with whether the pattern of loadings of the measurement items corresponds to the theoretically anticipated factors. Once the reliability and the validity test were done, the data that was collected through the confirmatory survey was used to test the hypothesis, H1: The purchase decision is a second order one dimensional construct comprising of three important reflective components: Personal, Cue utilization and Surrogate factors. A value of AVE higher that 0.5 indicates that there is a strong relationship between the constructs as argued by Chin (1995). Therefore the hypothesis is accepted. A set of 28 reliable, valid and parsimonious items were found out in this research which can be used by the hotels to scale the IHTAs as to what factors influence their purchase decisions. The scale is tested for convergent, discriminant and nomological validities, thereby extending and adapting the surrogate construct in purchase decision. Â  The researcher hopes that the above findings will add value to the luxury hotel business. The researcher also hopes that this research will generate some motivation for future researchers to otherwise scant and scarce pool of research in the area of hospitality.